Evaluation of the CGIAR Research Program: Policies, Institutions and Markets (PIM) - Gerrard, Chris; Andersson, Krister; Nankhuni, Flora; Spriggs, John (CGIAR Independent Evaluation Arrangement, 2014)
The CGIAR Research Program on Policies, Institutions and Markets (PIM) (http://www.pim.cgiar.org/) is led by IFPRI and implemented with the participation of 11 CGIAR Centers, making it the second most that involves the largest number of Centers.